Body position does not influence muscle oxygenation during submaximal cycling. Issue 2 (16th October 2020) - Wiggins, Chad C.; Baker, Sarah E.; Shepherd, John R. A.; Uchida, Koji; Joyner, Michael J.; Dominelli, Paolo B.
Abstract : Aerodynamic cycling positions reduce air resistance by minimizing body surface area yielding a lower power output required to maintain a given velocity. We evaluated the effect of aerobar vs upright cycling position on cardiorespiratory and muscle oxygenation measures during stationary (no air resistance) cycling exercise. We hypothesized that the aerobar position would reduce tissue oxygenation of the vastus lateralis (VL) during submaximal workloads. Fifteen endurance‐trained participants (9M/6F) completed constant load cycling at 20%, 40%, and 60% of peak power output (PPO) alternating between upright (UP) and aerobar (AERO) positions. Cardiorespiratory, near‐infrared spectroscopy (NIRS), and electromyography (EMG) measurements of the VL were performed. Body position had no effect on any NIRS‐derived parameters of the VL. At 40 and 60% PPO, the AERO position resulted in higher V ˙ O 2 (AERO: 2.33 ± 0.47 l·min −1 vs UP: 2.29 ± 0.44 l·min −1 for 40%PPO; AERO: 3.25 ± 0.67 l·min −1 vs UP: 3.19 ± 0.64 l·min −1 for 60%PPO), and minute ventilation ( V ˙ E ) at 60%PPO only (AERO: 90 ± 17 l·min −1 vs UP: 85 ± 15 l·min −1 ). In conclusion, body position does not affect VL oxygenation during submaximal workloads. However, the AERO position resulted in higher V ˙ E and V ˙ O 2 . When determining the ideal posture, cyclists should consider the need to balance reduced air resistance vs. maximizing metabolic resources.